2005
DOI: 10.1021/cm0483792
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hierarchical Assembly of Rhodium Nanoparticles into Spherical Aggregates and Superlattices

Abstract: Reduction of aqueous RhCl 3 with NaBH 4 in the presence of poly(vinyl pyrrolidone) (PVP) yields dense spherical nanostructures. The spherical aggregates, which generally have diameters between 10 and 100 nm, are built from smaller 1-3 nm Rh particles. The dense nanostructures are thermally stable beyond 100 °C, and they have a tendency to form ordered superstructures upon drying. Combining sodium n-dodecyl sulfate (SDS) with PVP modifies the size and morphology of the primary 1-3 nm particles, but does not cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
97
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 66 publications
7
97
1
Order By: Relevance
“…It has been shown that PVP is less effective as a stabilizer in a polar medium such as water [17][18][19]. The small particles have a higher chemical potential due to a large surface area-to-volume ratio, and particle attachment can reduce surface energy by reducing the surface area.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PVP is less effective as a stabilizer in a polar medium such as water [17][18][19]. The small particles have a higher chemical potential due to a large surface area-to-volume ratio, and particle attachment can reduce surface energy by reducing the surface area.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, the fabrication of hierarchical and complex nano-/microstructures that assemble from nanoparticles, nanorods, nanoribbons or nanobelts as building blocks at different levels have been proposed and partially realised in recent years. [2][3][4][5] These novel architectures should facilitate a deeper understanding of the "bottom-up" approaches and offer opportunities in searching for exciting new properties of materials, and be useful for fabricating functional nanodevices, and so forth. [5][6][7] Until now, some kinds of compounds or materials, such as metal oxides, [8] sulfides, [7,9] hydrates [10] and other compounds, [11] have been synthesised with controlled hierarchical/complex morphologies by various methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, other scenarios of controlled clustering of particles have been elaborated. [5][6][7][8][9][10][11] Concerning 3D-assemblies, the realization of ''colloidal molecules'' reminding the spatial regularity of chemical bonds between atoms was made possible using emulsions droplets filled up with colloidal particles [12] or by the control of the density of polymerization nucleation sites at the surface of inorganic colloids. [13] Glotzer and Solomon [14] have reviewed the engineering of anisotropic constructs built on the paradigm of ''bricks and mortar'' suggested by Boal and coworkers.…”
mentioning
confidence: 99%